Pengaruh Current Ratio, Debt to Equity Ratio dan Return On Equity terhadap Financial Distress Pada Perusahan Sub Sektor Dagang - Shofiyah Nur Aini (Jurnal Ekonomi dan Bisnis Digital, 2024)
Abstract This research aims to determine the influence of the Current Ratio, Debt to Equity Ratio and Return on Equity Ratio on the Interest Coverage Ratio in Trading Companies. Using a purposive sampling technique. The sample population was 5 trading companies listed on the Indonesian Stock Exchange in 2020-2023. The analysis method used is the panel data regression method. The testing in this research uses the Stata application version 17. The results of the research show that partially (T test) the Current Ratio has an influence, the Debt to Equity Ratio and the Return on Equity Ratio do not have a significant effect on Return On Equity. Other research results, namely Simultaneously, show that (F test) or together the Current Ratio, Debt to Equity Ratio and Return on Equity Ratio do not have a significant effect on the Interest Coverage Ratio in Trading Companies listed on the Indonesian Stock Exchange in 2020-2023